Philosophical foundations of criminal law - Duff, Antony; Green, Stuart P. (Oxford : Oxford University Press, 2011)
This volume gathers leading theorists to present original work on a range of foundational questions in criminal law theory. It provides an overview of current philosophical work on the criminal law, setting an agenda for further research and debate.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Criminal law -- Philosophy; Law